New-Onset Hyperreligiosity, Demonic Hallucinations, and Apocalyptic Delusions following COVID-19 Infection - Ahearn, Joseph; Driscoll, Maggie; Gilela, Sahiti (Case Reports in Psychiatry, 2023)
Background. Neuropsychiatric sequelae of COVID-19 have been documented, including delusions, hallucinations, agitation, and disorganized behavior. Although the mechanisms for these symptoms remain unclear, there has been an increasing body of literature suggesting a correlation between COVID-19 infection and psychosis. Here, we illustrate the case of a 34-year-old female with no previous psychiatric history who contracted COVID-19 and subsequently developed severe symptoms of psychosis. After presenting to the emergency department with one month of worsening mood, auditory hallucinations, intrusive thoughts, and hyperreligiosity, she was admitted to the inpatient psychiatric unit. The patient was treated with multiple antipsychotic medications and was discharged in stable condition with resolution of her auditory hallucinations; however, her delusions, hyperreligiosity, and negative psychotic symptoms persisted, resulting in a second inpatient psychiatric admission eight days after discharge, during which she again did not reach full remission. Objectives. With this information, we hope to increase awareness of COVID-induced psychosis and further discuss the relationship between COVID-19 infection and neuropsychiatric symptoms. Conclusions. Although there has been increasing research about the COVID-19 pandemic, there is much to be elucidated regarding the neuropsychiatric symptoms related to these infections. Similar to previous studies, our case describes a patient with no previous psychiatric history who developed severe psychotic symptoms after COVID-19 infection and was admitted to the inpatient psychiatric unit. These symptoms resulting from infection can be severe or debilitating for the patient. Therefore, physicians should be aware of these potential neuropsychiatric sequelae when treating patients with active COVID-19 infections, and treatment with antipsychotics or acute inpatient psychiatric admission should be considered.